Identification of empagliflozin-related hub genes in atherosclerosis and their correlations with immune infiltration: Network pharmacology and bioinformatics analyses - Yicheng Rong; Xinyu Liu; Yuanyuan Sun; Le Yang; Liming Chen (PLoS ONE, 2026)
Background Atherosclerosis (AS) is by far the most frequent underlying cause of atherosclerotic cardiovascular disease. Recently, sodium-glucose cotransporter 2 (SGLT2) inhibitors stand out for their anti-atherosclerotic effects. The present study was conducted to explore the potential genetic and molecular mechanisms of empagliflozin, a selective SGLT2 inhibitor, in preventing AS, and the correlation of empagliflozin-related hub genes with immune cells. Methods In our study, pharmacology platforms were accessed to identify the empagliflozin-related genes (ERGs). AS datasets GSE100927 and GSE43292 were downloaded from the public GEO database to identify AS-differentially expressed genes (AS-DEGs). Furthermore, the empagliflozin-related DEGs (ERDEGs) were obtained by intersecting AS-DEGs and ERGs. ERDEGs were further analyzed for Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. The protein-protein interaction (PPI) network was constructed to screen for hub genes, which were subjected to regulatory network construction, ROC curve plotting, as well as validation analysis, correlation and Friends analysis, and CIBERSORT and ssGSEA analysis. Results A total of 33 genes were identified as ERDEGs, among which the empagliflozin-related hub genes were identified to be IL1B, EGFR, ERBB2, JAK2, SYK, and LGALS3 in AS. Furthermore, in terms of the characteristics of immune cells, there were significant correlations between ERBB2 and CD8 + T cells, IL1B and resting mast cells, LGALS3 and eosinophils, as well as JAK2 and CD56dim NK. Conclusion Our network pharmacology and bioinformatics analyses provide a comprehensive understanding of the potential mechanisms of empagliflozin in AS at the genomic level, with the discovery of significant correlations between the screened hub genes and various immune cell subsets.